The Role of Promotional Deception in Influencing Voters’ Decisions (A Case Study of Iraqi Society) - Yaseen Ali Hameed Alkubeisy; Sabah Mohammed Obaid; Anwer Salam Hafedh (Global Academy of Business Studies, 2026)
Purpose: This study examines how promotional deception shapesvoters' decisions in Iraqi society, an emerging democracy markedby political fragmentation, identity-based voting, and unevenmedia literacy. It investigates four dimensions of promotionaldeception, namely misleading information, emotionalmanipulation, fake news, and unrealistic electoral promises, andtheir influence on voter decisions.Methodology: A descriptive analytical design was adopted usinga structured questionnaire administered to 100 Iraqi voters fromvaried educational and occupational backgrounds. Data wereanalyzed in SPSS through descriptive statistics, Cronbach's alphareliability testing, an independent samples t-test, Pearsoncorrelation, and simple linear regression to test the hypothesizedrelationship between promotional deception and voter decisions.Results: Findings confirm a statistically significant positive effectof promotional deception on voter decisions. Social mediaemerged as the principal channel for disseminating misleadingcontent, emotional manipulation exerted the strongest influenceamong the four dimensions, and respondents displayed onlymoderate media literacy.Conclusions: Promotional deception measurably distorts rationalelectoral judgment among Iraqi voters, reinforcing emotionallydriven rather than policy-based decisions and exposing thefragility of informed citizenship within a consolidatingdemocracy.Limitations: The cross-sectional design and conveniencesampling restrict causal inference and generalizability beyond thesurveyed population.Contributions: The study extends political marketing theory toan underexamined Middle Eastern context and offers evidencebased guidance for regulators, educators, and electoral institutionsstrengthening media literacy and transparency.